Pengembangan Aplikasi RATU LIAN (Operasi Hitung Perkalian) Berbasis Android sebagai Suplemen Pembelajaran untuk Meningkatkan Keterampilan Berhitung Peserta Didik Kelas IV - Sheila Arisa Putri; Krisma Widi Wardani (Jurnal Ilmiah Wahana Pendidikan, 2022)
The purpose of this study was to determine the feasibility of the RATU LIAN learning android-based application (Multiplication Count Operation) as a learning supplement to improve the numeracy skills of fourth grade elementary school students. This research uses research and development methodology or Research and Development (R&D) which applies the ADDIE development model. Interviews and questionnaires were used as data collection methods. As for this study, experts are used as a source of research data. The product development steps are (1) analyzing the problem, (2) drafting, (3) making, validating the product, and revising the product (4) implementing the product and (5) evaluating the product. In this study, the analysis technique used percentage and categorical descriptive techniques. The validation results of media experts show that this application obtains a final percentage of 86.5% and is included in the very valid category to use. The results of the final percentage of the material expert validation test, namely 97.9%, are included in the very valid category. As well as the results of the responses of 2 fourth grade elementary school teachers to the RATU LIAN application (Multiplication Count Operation), namely obtaining a final percentage of 96.2%. It can be concluded that the RATU LIAN application (Multiplication Count Operation) is very valid to be used as a learning supplement to improve numeracy skills